The Prevalence of Hypertriglyceridemia, and Hyperuricemia in Libyan Adults diagnosed with Coronary Artery Disease, Type 2 Diabetes, and Hypertension: A Cross-Sectional Study - Ali Fadhlullah; Ahmed Balha; Razk Abdalgwad (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and aims. Coronary artery disease (CAD) is associated with increased morbidities and mortalities and has become increasingly prevalent especially in those who have already had predisposing factors such as T2DM and hypertension. We firstly aimed to determine the prevalence of hypertriglyceridemia, and hyperuricemia in Libyan adults with CAD combined with T2DM and hypertension. Then, we secondly aimed to examine the prevalence of T2DM, hypertension, hypertriglyceridemia, and hyperuricemia in all patients with established CAD. Methods. This was a retrospective cross-sectional study of Libyan adults with established CAD. Descriptive statistics was used to interpret the prevalence of T2DM, hypertension, hypertriglyceridemia, and hyperuricemia in patients with CAD. Prevalence was calculated using the following equation :(Prevalence= Number of cases/ Total number of participants in the study*100). Results. In total, 49 patients with CAD combined with T2DM and hypertension were included in the study. 28 (57.1%) were females, and 21 (42.9%) were males. The mean age was 60 ± 11.89 years. The prevalence of hypertriglyceridemia was much higher than hyperuricemia in patients with CAD combined with T2DM and hypertension at 44 (89.8%) and 33 (67.3%), respectively. Moreover, in all patients with CAD (N = 97) hypertriglyceridemia still the highest prevalence at 81(83.5%), followed by T2DM at 69 (71.1), respectively. Conclusion. We have found amongst Libyan patients with CAD that hypertriglyceridemia had the highest prevalence followed by T2DM, then hyperuricemia, while hypertension had the lowest prevalence. Further studies are needed to focus in more details on these outcomes maybe in larger number of patients with established CAD.